IMPROVING INDONESIAN LEARNING OUTCOMES USING THE AUDIOLINGUA METHOD IN ELEMENTARY SCHOOL STUDENTS - Muhammad Yusnan; Rimayasi; Karim Karim; Risman Iye (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
Learning outcomes can be interpreted as learning consequences in the form of information, mastery, or skills, and attitudes acquired by students during academic lessons and expressed in numbers. The purpose of this study was to find out how the Application of Fun Learning Methods in Improving Student Learning Outcomes in Class IV Indonesian Language at Wameo 2 Public Elementary School. This research was conducted through the process of planning, implementing, observing and evaluating. The subjects in this study were 15 grade 3 students of School Students Country 2 Wameo The results of this study indicate that the pre-cycle has not shown learning outcomes, after using the Audiolingua method in Cycle I and Cycle II there is an increase in Indonesian learning outcomes using the Audiolingua method